Implementasi Inovasi Produk Pada DKM Cakes & Cookies - Edy Wahyudi; Wheny Khristianto; Frisca Intan Syafarina (Journal of Economic, Management and Entrepreneurship, 2024)
This research aims to describe product innovation carried out by one of the in this study are the owner as a key informant operational director and consumers in relation to product innovation. The data analysis used is domain analysis and taxonomy analysis. The result of this study are that DKM Cakes & Cookies has implemented 5 bases of product innovation, namely modulation-based innovation, size-based innovation, packaging-based innovation complementary material development-based innovation, effort reduction-based innovation The phenomenon that occurs shows that the product innovation most often carried out by DKM Cakes & Cookies is complementary material development-based innovation by producing more than 100 menu variations and creating limited edition products that are only sold once a year with a different product selection every 1 month, which is named dynamite products.